Potencial do sensoriamento remoto aéreo e orbital na análise do manejo integrado do fogo: um estudo de caso no Parque Nacional Chapada dos Guimarães, Mato Grosso - Costa, João Vitor Silva (2023)
Fire is an element of great protagonism in the Cerrado. It occurs naturally since the beginning of the biome, playing an important role in the maintenance of this rich ecosystem. With the intensification of the anthropic occupation process, which started in the mid-1950s, the recurrence of forest fires grew excessively, largely due to the use of fire as a conversion tool. In the period from 1985 to 2020, approximately one third of the Cerrado territory experienced some fire event, with areas with very high recurrence. Years with more than 10 million hectares burned have been recorded. In recent years, environmental managers have started to adopt the prescribed burning practice, not only for building firebreaks, but also as a way to control the amount of vegetation biomass, which is the fuel for forest fires. This and other practices make up the Integrated Fire Management. In this context, this project aims to understand the potential of aerial and orbital remote sensing in the analysis of Integrated Fire Management, using time series of satellite images, and data obtained in loco by the Remotely Piloted Aircraft System (RPAS). The results achieved showed better potential in the use of Drones due to the level of detail of the data, capable of providing information at the understory level. This detail becomes more important when fire management is carried out at the beginning of the dry season, and biomass control is lower. It is worth mentioning that, even less effective in analyzing early burning, the satellite images, Sentinel-2, had satisfactory results for analyzing burning in the months of June and July, registering a correlation between data of R² = 0.71.